Antimicrobial, shelf-life stability, and effect of maltodextrin and gum arabic on the encapsulation efficiency of sugarcane bagasse bioactive compounds (2021)
ABSTRACT: This study shows the effects of maltodextrins and gum arabic as microencapsulation agents on the stability of sugarcane bagasse extracts and the potential use of the extracts as antimicrobial agents. The bioactive compounds in sugarcane bagasse (SCB) were extracted using 90% methanol and an orbital shaker at a fixed temperature of 50 ◦C, thereby obtaining a yield of the total phenolic content of 5.91 mg GAE/g. The bioactive compounds identified in the by-product were flavonoids, alkaloids, and lignan (-) Podophyllotoxin. The total phenolic content (TPC), antioxidant activity, and shelf-life stability of fresh and microencapsulated TPC were analyzed. This experiment’s optimal microencapsulation can be obtained with a ratio of 0.6% maltodextrin (MD)/9.423% gum arabic (GA). Sugarcane bagasse showed high antioxidant activities, which remained stable after 30 days of storage and antimicrobial properties against E. coli, B. cereus, S. aureus, and the modified yeast SGS1. The TPC of the microencapsulated SCB extracts was not affected (p > 0.05) by time or storage temperature due to the combination of MD and GA as encapsulating agents. The antioxidant and antimicrobial capacities of sugarcane bagasse extracts showed their potential use as a source of bioactive compounds for further use as a food additive or nutraceutical. The results are a first step in encapsulating phenolic compounds from SCB as a promising source of antioxidant agents and ultimately a novel resource for functional foods.